2014
DOI: 10.4172/2157-7412.1000218
|View full text |Cite
|
Sign up to set email alerts
|

Significant Increase of IL-8 Sputum Levels in Treatment Resistant Severe Asthma Compared with Difficult to Treat Severe Asthma Patients

Abstract: The spectrum of severe asthma includes different groupings and phenotypes. World Health Organization proposes to differentiate two categories: difficult-to-treat-severe asthma (DTTSA) and treatment-resistant-severe asthma (TRSA). DTTSA includes controllable severe asthma and TRSA includes patient's not achieving adequate levels of control and persisting indicators of severity despite receiving and using maximum levels of inhaled medications. We hypothesized that granulocyte counts from sputum samples could dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…IL-17A orchestrate the neutrophilic influx into the airways [22], but on other hand there are growing evidence that IL-17A enhance Th2 mediated immune response [10,24,25]. Other potent chemoattractant of neutrophils in the airways is IL-8 [26], found to be elevated in serum [27], BAL [8] and sputum of treatment-refractory severe asthma [28].…”
Section: Introductionmentioning
confidence: 99%
“…IL-17A orchestrate the neutrophilic influx into the airways [22], but on other hand there are growing evidence that IL-17A enhance Th2 mediated immune response [10,24,25]. Other potent chemoattractant of neutrophils in the airways is IL-8 [26], found to be elevated in serum [27], BAL [8] and sputum of treatment-refractory severe asthma [28].…”
Section: Introductionmentioning
confidence: 99%
“…IL-8 is a chemokine of EOS and neutrophils, which play a decisive role in asthma aggravation, severe asthma, refractory asthma and hormone-resistant asthma, and promote the occurrence of airway remodeling by increasing the migration and proliferation of ASMCs. Studies revealed that (8,9) in patients with severe resistant asthma, the level of IL-8 was significantly increased in sputum, and IL-8 could enhance the contraction of ASM by increasing the expression of L-shaped Ca 2+ . More interestingly (10), asthma, which is mainly characterized by neutrophil inflammation, has an increased bacterial load and a unique microbiota composition, and is accompanied by excessive inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…Glucocorticoid is the first choice of drugs for asthma prevention and treatment, which can effectively inhibit airway inflammation and the proliferation of ASMCs, and reduce AHR (7). Patients with severe or refractory asthma have poor treatment outcomes, despite adhering to highdose inhaled corticosteroids, resulting in persistent or recurrent symptoms (8). Repeated exposure to allergens can cause glucocorticoid insensitivity in asthmatic mice (9).…”
Section: Introductionmentioning
confidence: 99%
“…Two possible phenotypes based on the inflammatory process have been proposed: Th2 asthma, which is characterized by relatively higher blood eosinophilic counts and higher exhaled nitric oxide (FeNO, which is produced by the Th2-regulated nitric oxide synthase enzyme), and non-Th2 asthma, which is typified by relatively lower eosinophils counts and lower FeNO [1,2]. These two phenotypes respond very differently to treatment with inhaled corticosteroids [3], and the airway microbiota might be one possible explanation for this. With the polymerase chain reaction (PCR) and 16s RNA gene-sequencing techniques, differences in the microbiota between asthma phenotypes [4][5][6][7][8] and allergic inflammations [2,9] were previously identified.…”
Section: Introductionmentioning
confidence: 99%